2016
DOI: 10.1590/1413-81232015211.16802014
|View full text |Cite
|
Sign up to set email alerts
|

Tabagismo e pobreza no Brasil: uma análise do perfil da população tabagista a partir da POF 2008-2009

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
23

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 8 publications
3
16
0
23
Order By: Relevance
“…Regardless, the impact that spending has on overall family income appears to differ across income brackets, given that higher-income individuals spend proportionately less on tobacco products, while having greater access to resources for smoking cessation. (29) When analyzing smoking among industrial workers in Brazil by geographic region, we found that, for both genders, workers in the northeastern region were at a lower risk of smoking than were those in the southeastern region. In addition, among women, those in the northern region of the country were at a lower risk of smoking than were those in the southeastern region.…”
Section: Discussionmentioning
confidence: 88%
“…Regardless, the impact that spending has on overall family income appears to differ across income brackets, given that higher-income individuals spend proportionately less on tobacco products, while having greater access to resources for smoking cessation. (29) When analyzing smoking among industrial workers in Brazil by geographic region, we found that, for both genders, workers in the northeastern region were at a lower risk of smoking than were those in the southeastern region. In addition, among women, those in the northern region of the country were at a lower risk of smoking than were those in the southeastern region.…”
Section: Discussionmentioning
confidence: 88%
“…Ressalta-se, a princípio, que a pessoa tabagista é assim considerada quando gasta parte da sua renda com esse produto e derivados. E, atualmente, em torno de 10% da população brasileira tem gastos financeiros de aproximadamente 1,5% da sua renda, sendo esta população majoritariamente masculina (15) .…”
Section: Discussionunclassified
“…Dentre as estratégias para intervenção, as focadas em grupos específicos, com suporte cognitivo e comportamental, são essenciais para promover o sucesso na cessação do tabagismo (15) . A elaboração de subgrupos pode contribuir para o sucesso das abordagens, uma vez que os fatores motivacionais, apesar de variarem de pessoa para pessoa, podem partir de experiências prévias comuns.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Homens ( Bazotti et al (2016) analisou a Pesquisa de Orçamentos Familiares (POF) de 2008-2009 e demonstrou que aproximadamente 10% da população brasileira apresenta gastos com produtos relacionados ao tabaco. Em geral, a maioria dos pacientes tabagistas possuem baixas renda e escolaridade, idade mais avançada e são predominantemente do sexo masculino.…”
Section: Mulheres (N=67)unclassified